Evaluating market access and food consumption trends in rural communities: insights from a high-frequency integrated market survey in Bangladesh - Faijul Kabir, A.N.M.; Ahmed, Sharif; Veettil, Prakashan Chellattan; Krupnik, Timothy J. (TAFSSA, 2024)
This research note provides a comprehensive analysis of food consumption and dietary patterns, utilizing high-frequency data from consumers and various markets. It underscores TAFSSA’s (Transforming Agri-Food Systems in South Asia) commitment to the food production-to-consumption continuum, emphasizing equitable access to sustainable and healthy diets. The study delves into the dynamics of food systems and market trends in Northern Bangladesh, focusing on four districts—Rajshahi, Chapai Nawabganj, Rangpur, and Dinajpur. The research examines price fluctuations when locally produced diversified foods, enter the market. These findings highlight the benefits of crop diversification for farmers and its impact on local and regional market dynamics. Data for this research note is derived from a biweekly high-frequency survey conducted over a year, starting in August 2023. It provides preliminary insights into consumer food consumption and dietary patterns, the production of diversified crops price trends over time, and their impact on local food systems.